2020
DOI: 10.1111/hdi.12871
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between lung ultrasonography and current methods for volume assessment in Asian chronic hemodialysis patients

Abstract: Introduction: Volume assessment in end-stage kidney disease patients on hemodialysis (HD) remains inadequate by existing methods: clinical examination, bioimpedance spectroscopy, measurement of inferior vena cava diameter by ultrasound (IVCD), and plasma B-type natriuretic peptide (NT-pro BNP). This study aims to compare the performance of lung ultrasound against existing methods for volume assessment in a HD cohort. Methods: Two nephrologists independently performed 28-point lung ultrasound immediately before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 39 publications
4
9
0
Order By: Relevance
“…In a recent study investigating the role of B-lines in the assessment of volume variation in hemodialysis patients, there was a moderate negative correlation with the IVC CI index. 26 Analysis of the ROC curve in the present study showed a good to an excellent performance of LUS in predicting lung congestion. The performance of B-lines as predictors for lung congestion was assessed by some previous studies in patients with several clinical conditions.…”
Section: Discussionsupporting
confidence: 60%
“…In a recent study investigating the role of B-lines in the assessment of volume variation in hemodialysis patients, there was a moderate negative correlation with the IVC CI index. 26 Analysis of the ROC curve in the present study showed a good to an excellent performance of LUS in predicting lung congestion. The performance of B-lines as predictors for lung congestion was assessed by some previous studies in patients with several clinical conditions.…”
Section: Discussionsupporting
confidence: 60%
“…33 Previous studies have compared several methods for dry weight guidance in HD patients which demonstrated the promise of the LUS-guided technique as an increase of TLUSS correlated with interdialytic weight gains, and a reduction of B-lines possibly related with lost volumes during HD including inferior vena cava diameters and atrial dimensions. 15,21,25,31,[34][35][36] Torino et el, evaluated the fluid accumulation by using physical examination, ie, standardized lung auscultation and quantification of peripheral edema compared with LUS which found that lung crackles, either alone or in combination with peripheral edema, poorly reflected the interstitial lung edema in HD patients and these findings support using add-on LUS to evaluate fluid accumulation and lung congestion. 12 This study supported an insensitivity of the clinical signs and a value of LUS-guided treatment by achievement of target weight by reduction of prescribed dry weight if moderate pulmonary congestion was presented (TLUSS ≥16) resulting in controllable pre-HD, SBP, MAP and reduction of heart size and NT-proBNP levels.…”
Section: Discussionmentioning
confidence: 95%
“…Noble et al in a quantitative analysis of a small sample of patients found that for every 500 ml ultrafiltration, the number of B-lines decreased by about 2.7 [18]. Ngoh et al found that despite the elimination of body fluids, the NT-pro BNP and bioimpedance spectrum index increased inexplicably after dialysis [19]. This means that the current capacity evaluation methods have a reduced ability to detect changes of liquid state after hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the B-line dialysis process were correlated with ultrafiltration volume and weight loss [6,[8][9][10]. Furthermore, the B-line level were significantly correlated with other capacity evaluation indicators (e.g., the bioimpedance spectroscopy indicators, inferior vena cava diameter and NT-proBNP) [5,11,19].…”
Section: Discussionmentioning
confidence: 99%